Mini Review: Production and Economics Analysis Of Backyard Production of Tiger Grouper Epinephelus Fuscoguttatus Fingerlings in Situbondo, Indonesia - Romi Novriadi (Universitas Sriwijaya, 2019)
Application of backyard technology to produce tiger grouper fingerlings in the area of Situbondo is examined with emphasis on production system and economic structure. Complete hatcheries production system that employ full production systems from broodstock, maturation, spawning, larviculture and early nursery phase are common in this area. Natural spawning activities without the use of hormone or another chemical substance become the primary method to produce the larvae. Hatchery in Situbondo typically consist with concrete tank to culture the larva, sand filter and live food production tanks, including phytoplankton production system. While the nursery production system as an intermediate step between hatchery and grow-out production consist with concrete tank and grading system to reduce the size variation, cannibalism and to ensure there is no more than 30% difference in total length between the grade sizes within the culture tanks. The output of the economic analysis showed that with final survival rate about 10%, farmer in Situbondo still get a good annual return through the sales of fingerlings. From this situation, farmer still obtain high cash flow from backyard production system and about 69.06% rate of return to capital. Overall, backyard technology consists with hatchery and early nursery production system provide potential sources for poverty alleviation and support the sustainability of aquaculture production in Situbondo. Good economic structure and opportunity to participate in several government programs speed up the adoption of this technology and become an important chain for tiger grouper production system in Indonesia.